Smart city trends: A focus on 5 countries and 15 companies. (April 2022) - Kim, JungHoon
Abstract: Smart city services offer effective solutions to urban problems. Thus, many countries are introducing smart city services, and some companies are entirely focused on developing the technology for the services. However, the classification of smart cities based on how they are developed is currently underexplored. This study analyzes smart cities built and operated by major countries and companies within the smart city framework. Firstly, the direction of smart city development in each city is changing. In the past, the goal of a smart city was to build urban infrastructure. However, the current focus is on providing smart city services. Thus, the operation and maintenance of smart city services are becoming more important than building them. Secondly, the manner in which companies secure smart city services has become diverse. As such, companies may be classified into those that secure the entire value chain of smart cities and those that own only some smart city services. Thirdly, companies are actively establishing a cooperative system to secure smart city technology. Rather than developing all the required technology, they demonstrate flexibility in responding to various smart city needs by collaborating with companies that provide individual services. Highlights: Smart city services are an effective solution to solve urban problems. The direction of smart city development in each city is changing. The operation and maintenance of smart city services are becoming more important. Companies can be classified into secure the entire value chain services of smart city and own only some services of smart city. Companies are becoming more active in establishing a cooperative system to secure smart city services.